Assessment of the ablation characteristics of carbon/phenolic composites using X-ray microtomography. (29th September 2019) - Cheon, Jae Hee; Shin, Eui Sup
Abstract: In this study, the ablation characteristics of carbon/phenolic composites were evaluated using X-ray microtomography. The ablation tests of carbon/phenolic composites were performed using a 0.4 MW arc-heated wind tunnel, and the composite samples were scanned using micro-computed tomography (Micro-CT) to analyze the ablation characteristics according to the duration of the ablation test. Through calibration of the scanned raw images, ~2, 000 cross-sectional images were generated with micrometer level intervals. Using these obtained cross-sectional images, the porosity and density distributions in the longitudinal direction of the samples were calculated. The mass was then calculated using the analyzed porosity and density, and gave an error of 0.1–3.4% compared to the mass measured using an electronic balance. Our observations indicate that the physical properties of carbon/phenolic composite samples can be calculated using X-ray microtomography, and we expect that our results will be useful in analyzing the behavior of ablative composites.